‘Gerobok Rezeki #BPACare’ Project launched - UMP, PNC (2018)
Concerned with the issue of the students, Universiti Malaysia Pahang (UMP) launched a project called ‘Gerobok Rezeki #BPACare’ in conjunction with the Academic Management Division Open Day 2018 (HTBPA) at UMP Gambang Campus on October 3, 2018.